The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1523/jneurosci.4756-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence for Chronic Demyelination in Spared Axons after Spinal Cord Injury in a Mouse

Abstract: The pattern of remyelination after traumatic spinal cord injury remains elusive, with animal and human studies reporting partial to complete demyelination followed by incomplete remyelination. In the present study, we found that spared rubrospinal tract (RST) axons of passage traced with actively transported dextrans and examined caudally to the lesion 12 weeks after mouse spinal cord contusion injury were fully remyelinated. Spared axons exhibited a marginally reduced myelin thickness and significantly shorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
137
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(151 citation statements)
references
References 59 publications
8
137
2
Order By: Relevance
“…Tissues were prepared as described previously (28). Briefly, three injured mice were killed and perfused at 3 MPV with ice-cold 3% (wt/vol) paraformaldehyde/0.5% glutaraldehyde.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tissues were prepared as described previously (28). Briefly, three injured mice were killed and perfused at 3 MPV with ice-cold 3% (wt/vol) paraformaldehyde/0.5% glutaraldehyde.…”
Section: Methodsmentioning
confidence: 99%
“…In short, we cannot be sure that all abnormally thin or short myelin is regenerated, nor that all sheaths with normal dimensions are a product of development rather than regeneration. Myelin sheath dimensions affect signal conduction speed considerably, and sluggish conduction following insult has been attributed in part to irregular remyelination (11,12,(26)(27)(28)(29). A better comprehension of these fundamentals is essential in guiding a new understanding of spontaneous myelin regeneration and therapeutic approaches to demyelinating disorders.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When demyelination is induced by toxins injurious to oligodendrocytes and myelin (e.g., by dietary cuprizone or direct delivery of lysolecithin or ethidium bromide), the remyelination usually proceeds to completion, albeit in an age-dependent manner (Blakemore and Franklin 2008). Similarly, there is evidence that axons undergoing primary demyelination in experimental or clinical traumatic injury undergo complete remyelination, and that the persistence of chronically demyelinated axons is unusual (Lasiene et al 2008). An exception is when demyelination is induced by, or associated with, the adaptive immune response, such as occurs in the autoimmune-mediated condition multiple sclerosis (MS) and its laboratory animal model, experimental autoimmune encephalomyelitis (EAE).…”
Section: Remyelination Is the Normal Response To Demyelinationmentioning
confidence: 99%
“…In animal models, chronic demyelination has been described (Gledhill et al, 1973;Blakemore, 1974;Gledhill and McDonald, 1977;Blight, 1983;Totoiu and Keirstead, 2005) while little chronic demyelination is reported in humans (Gensert and Goldman, 1997;Kakulas, 1999;Guest et al, 2005). However, recent evidence has suggested that remyelination is far more extensive in animal models when accounting for which axons remain spared and traverse the lesion (Lasiene et al, 2008).…”
Section: Clinical Significance Of Ol Lossmentioning
confidence: 99%